Partisipasi Masyarakat Dalam Program Keluarga Berencana Di Kecamatan Amuntai Utara - Irza Setiawan (FAKULTAS ILMU ADMINISTRASI UNIVERSITAS LANCANG KUNING, 2023)
There are 2,876 couples of childbearing age in North Amuntai sub-district and there are 2,219 active family planning users. The purpose of this study was to find out how community participation is in the family planning program in North Amuntai sub-district, the method uses a qualitative approach with secondary data analysis techniques, book literature and Combined with national journal data on population, couples of childbearing age and active family planning participants in North Amuntai District, it is known that community participation is more inclined to involve using pill and injection contraceptive programs, and only a few use long-term contraceptive methods